2013
DOI: 10.3945/ajcn.112.056689
|View full text |Cite
|
Sign up to set email alerts
|

Diet, microbiota, and microbial metabolites in colon cancer risk in rural Africans and African Americans

Abstract: Background: Epidemiologic studies have suggested that most cases of sporadic colon cancer can be attributed to diet. The recognition that colonic microbiota have a major influence on colonic health suggests that they might mediate colonic carcinogenesis. Objective: To examine the hypothesis that the influence of diet on colon cancer risk is mediated by the microbiota through their metabolites, we measured differences in colonic microbes and their metabolites in African Americans with a high risk and in rural n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
445
0
9

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 576 publications
(485 citation statements)
references
References 62 publications
(48 reference statements)
31
445
0
9
Order By: Relevance
“…47 NA had higher abundance of starch degrading gut bacteria (diet high in resistant starch), carbohydrate fermenters and butyrate producers and metabolites, while Americans had higher levels of potentially pathogenic proteobacteria (Escherichia and Acinetobacter) and bile acid deconjugators and their metabolic end products. 48,78 O'Keefe et al (2015) also measured colonic inflammation and found that it went below NA baseline when AA were placed on NA diet, while NA colonic inflammation went above AA baseline when NA were placed on AA diet. 48 Butyrate production was associated with lower mucosal proliferation both in NA consuming high-fiber diet and AA switched to NA diet.…”
Section: ¡mentioning
confidence: 99%
See 2 more Smart Citations
“…47 NA had higher abundance of starch degrading gut bacteria (diet high in resistant starch), carbohydrate fermenters and butyrate producers and metabolites, while Americans had higher levels of potentially pathogenic proteobacteria (Escherichia and Acinetobacter) and bile acid deconjugators and their metabolic end products. 48,78 O'Keefe et al (2015) also measured colonic inflammation and found that it went below NA baseline when AA were placed on NA diet, while NA colonic inflammation went above AA baseline when NA were placed on AA diet. 48 Butyrate production was associated with lower mucosal proliferation both in NA consuming high-fiber diet and AA switched to NA diet.…”
Section: ¡mentioning
confidence: 99%
“…Prior studies by the same group showed that significantly higher levels of total fecal bile acids in AA than NA, and DCA in particular was significantly correlated (r 2 D0.65; PD0.01) with baiCD gene abundance-a gene in the bile acid-inducible operon of bile acid 7a-dehydroxylating bacteria such as Clostridium scindens and related organisms responsible for DCA production. 78 In summary, we propose a novel mechanism to explain why consumption of a high red meat and saturated fat diet imparts risk for CRC development involving primary microbial risk factors (bile acid metabolizing and sulfidogenic bacteria) that are modifiable by diet (Fig. 3).…”
Section: ¡mentioning
confidence: 99%
See 1 more Smart Citation
“…A study of Native Africans and African Americans not only showed the genus Prevotella was higher in the former and Bacteroides more prevalent in the latter, but also showed higher diversity in the Americans supposedly because of a more diversified diet [59]. Although this study did not imply a more diverse microbiota is 'preferable' in terms of health, others have certainly implied this through association [60][61][62].…”
Section: Effects Of Diets On the Gut Microbiota In Five Continentsmentioning
confidence: 85%
“…Butyrate is preferred by colonic cells over circulatory glucose or glutamine, to obtain up to a 70% of energy needs. Butyrate is an important tumor suppressant molecule formed during fermentation and exerts selective functions in normal and tumor colon cells [24]- [26]. It promotes growth in normal cells, while inhibiting growth in colon tumor cells by promoting apoptosis and suppressing proliferation.…”
Section: Production Of Short Chain Fatty Acids (Scfa)mentioning
confidence: 99%